Diversity in morphology and pigmentation patterns of local Pabna cattle in Bangladesh - Talukder, Md Azharul Islam; Shahjahan, Md; Islam, Mohammed Sirajul; Munira, Sirazum (Research in Agriculture Livestock and Fisheries, 2017)
The study was aimed to reveal the morphological features of local Pabna cattle at Bangladesh Livestock Research Institute (BLRI), Regional Station, Sirajganj and community levels. Data of various morphological features were collected from total 24 cattle from on-station and 8 cattle from community. It was observed that most of the morphological features were not varied between the studied cattle populations except body length, height at wither, pelvic length, tail dock circumference and mouth circumference (p <0.05). Pigmentation pattern revealed that light red was dominated for coat color in both cattle population while black color was most frequently observed in muzzle, eyelid, eyelash, horn, hoof, dew claw and tail switch. As most of the phenotypic observation and pigmentation patterns were unique between two existing Pabna cattle population, an open nucleus breeding system might be enhanced the desire dairy breed development from those cattle population regarding the uniformity of morphological features. Res. Agric. Livest. Fish.4(3): 201-208, December 2017